2008
DOI: 10.1152/ajpendo.90372.2008
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of pulsatile glucagon counterregulation by switch-off of α-cell-suppressing signals in streptozotocin-treated rats

Abstract: Glucagon counterregulation (GCR) is a key protection against hypoglycemia that is compromised in diabetes via an unknown mechanism. To test the hypothesis that alpha-cell-inhibiting signals that are switched off during hypoglycemia amplify GCR, we studied streptozotocin (STZ)-treated male Wistar rats and estimated the effect on GCR of intrapancreatic infusion and termination during hypoglycemia of saline, insulin, and somatostatin. Times 10 min before and 45 min after the switch-off were analyzed. Insulin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(63 citation statements)
references
References 107 publications
8
55
0
Order By: Relevance
“…8 The postulated network 5 included relationships between the α cells, δ cells, BG, and switchoff signals (intrapancreatically infused α-cell inhibitors that are terminated during hypoglycemia). This network explained the repair of GCR in diabetic rats by switch-off signals by interpreting the GCR as a rebound or disinhibition effect.…”
Section: Construct Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…8 The postulated network 5 included relationships between the α cells, δ cells, BG, and switchoff signals (intrapancreatically infused α-cell inhibitors that are terminated during hypoglycemia). This network explained the repair of GCR in diabetic rats by switch-off signals by interpreting the GCR as a rebound or disinhibition effect.…”
Section: Construct Developmentmentioning
confidence: 99%
“…57 We have shown that a network based on the relationships mentioned earlier explains key experimental findings and have presented experimental evidence to support the proposed construct. 5,6 In particular, we have used differential equations-based modeling to show that the proposed network explains each of the following findings in diabetic rats: 6. Higher GCR response to insulin vs somatostatin switch-off and stronger glucagon suppression by somatostatin than by insulin before a switch-off.…”
Section: 13-21mentioning
confidence: 99%
See 3 more Smart Citations